PENGARUH KUALITAS KEHIDUPAN KERJA DAN KOMPENSASI TERHADAP KINERJA DENGAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (Studi Pada Pegawai UNNES Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to determine: the effect of the quality of work life and compensation on Organizational Citizenship Behavior (OCB), which is mediated by job satisfaction. The technique of testing data used in this study include validity, reliability, multiple regression analysis, model test, t test and mediation to test and prove the research hypothesis. Based on the results of the analysis and discussion shows that: Quality of work life and significant positive effect on Organizational Citizenship Behavior (OCB) employees. 2). Compensation positive and significant impact on Organizational Citizenship Behavior (OCB) employees. 3). The quality of working life and significant positive effect on employee performance. 4). Compensation positive and significant impact on employee performance Semarang State universities. 5). Organizational Citizenship Behavior (OCB) positive and significant impact on employee performance. Suggestions can be submitted is still the number of employees by inaccuracies in attendance, it is necessary to do coaching-coaching constructive work ethic so that the employee's performance will be better. Keywords: Quality of Work Life, Compensation, OCB, and employee performance